Relationship between noise exposure levels, noise-induced hearing loss and neurobehavioral performance among steel mill male workers - Eh Lai, Priya Rathanak (2017)
Noise at workplace not only can cause hearing problems but also affect the performance of workers. Noise especially within the confine of steel manufacturing cannot be avoided since the operation revolving around machineries, devices and process which emitted high level of noise reaching up to 115dB(A). Approximately half of the steel mill workforce in Malaysia were reported to endure noise induced hearing loss. Therefore, the purpose of this study is to determine the effect of noise exposure towards deterioration of hearing threshold and the effect on neurobehavioral performance among male workers in steel manufacturing industries. This comparative cross -sectional study which involved 295 male steel manufacturing workers was conducted in one of the renowned steel making industries in Kemaman, Malaysia. Data collection is comprises of Questionnaires Survey, Audiometric Test, Personal Noise Exposure Monitoring and Neurobehavioural Core Test Battery (NCTB).The noise exposure of workers were gauge through personal noise dosimeter and the prevalence of noise-induced hearing loss (NIHL) among the workers were identified through audiometric test. Subsequently noise-induced hearing loss influence on neurobehavioural performance (cognition attributes) was further investigate by utilizing a set of seven tests consist in the Neurobehavioural Core Test Battery (NCTB). The study, resulted in 109 respondents were identified as non-NIHL respondents and 186 respondents endured NIHL. There is a difference of hearing threshold level between non-NIHL and NIHL respondents. Hearing threshold of the NIHL respondents portrayed that hearing loss with median value of 25dB(A) occur at the higher fence of frequency which is 4000Hz and 6000Hz for both of the ears. There are also difference of neurobehavioural performance between non-NIHL and NIHL respondents for overall score of NCTB (p<0.001). Furthermore, within sets of seven NCTB, only Digit Span (p<0.001), Digit Symbol (p<0.001) and Pursuit Aiming (p=0.008) indicates significant difference between non-NIHL and NIHL respondents where neurobehavioral performance among the NIHL respondents are lower as compared to those non – NIHL. However, the result from the study shows that there are no significant difference between personal noise dosage exposure level between non-NIHL and NIHL respondents (z=-0.366, p=0.715).The study also demonstrates there are no significant difference between personal noise exposure level (Noise Dose) and neurobehavioural performance (Overall NTB Score) among non-NIHL (r=-0.061, p=0.513) and NIHL respondents (r=-0.012, p=0.870). Finally, the study suggested that risk factor to be considered in prediction model for Neurobehavioral Performance Score is category of NIHL cases for Digit Symbol, Digit Span and Overall NCTB Score. Whereas for Pursuit Aiming, the risk factor that played important roles is the age of the respondents. The findings in this study concluded that, noise may cause some impairment in the nervous system function towards worker in metallurgical industry. On top of auditory effect of the noise on the hearing ability, non-auditory effect which is the neurobehavioural performance is also deteriorate amongst workers. Therefore, besides deterioration of hearing threshold level, changes of neurobehavioural performance could be regarded as the early exposure manifestation of the occupational noise effect among steel mill workers.